Mr. Lemoncello's great library race - Grabenstein, Chris; Grabenstein, Chris (New York Random House, 2017)
"Mr. Lemoncello holds a contest for his young friends where they must race to bring interesting facts back to his library"--Provided by publisher.
Sequel to: Mr. Lemoncello's Library Olympics.
Includes bibliographical references (p. 276-277).
School Library Journal, July 2017
Booklist, August 2017
Kirkus Review, August 2017
5.4.
Keywords: Libraries -- Juvenile fiction; Contests -- Juvenile fiction; Books and reading -- Juvenile fiction; Eccentrics and eccentricities -- Juvenile fiction; Libraries -- Fiction; Contests -- Fiction; Books and reading -- Fiction; Eccentrics and eccentricities -- Fiction; Action and adventure fiction